Selecting Room-Temperature Ionic Liquids to Optimize Voltammetric Responses: The Oxidation of NADH - O'Mahony, A; Hardacre, C; Compton, R (2010)
The electrochemistry of nicotinamide adenine dinucleotide (NADH) in its reduced form was examined in two room-temperature ionic liquids (RTILs): 1-ethyl-3-methylimidazolium bis-(trifluoromethylsulfonyl)imide ([C2 mim] [NTf2]) and 1-butyl-3-methylimidazolium hexafluorophos-phate ([C4 mim] [PF6]). NADH oxidation has previously been studied in aqueous solution where it follows the pathway: one-electron oxidation to the NADH+ radical cation, deprotonation to produce the neutral NAD radical, then oxidation to the NAD+ cation. The electrochemistry of NADH was examined in [C2 mim] [NTf2] and [C4 mim] [PF6] at the bare Pt electrode (10 μm diameter): In [C 2 mim] [NTf2], no oxidation was observed; in [C 4 mim] [PF6], an oxidative signal was observed, which likely followed the pathway described above, where upon formation of the NADH+ radical cation, the [PF6] - anion (unlike the [NTf2] - anion) reacts with the proton to form HPF6, which decomposes. This demonstrates the tunability of RTILs, whereby the choice of one anion in an RTIL over another can promote a reaction. Poly(vinylferrocene) (PVF) was studied as a mediator for the NADH detection in both RTILs to attempt to lower the potential of NADH detection. The Pt electrode was modified with PVF, and the oxidation of PVF to PVF+ was observed in [C2 mim] [NTf2] and [C4 mim] [PF6], but no mediation of the NADH oxidation was observed. © 2010 The Electrochemical Society.